2012
DOI: 10.1007/s12026-012-8379-2
|View full text |Cite
|
Sign up to set email alerts
|

The unique role of dietary l-arginine in the acceleration of peritoneal macrophage sensitivity to bacterial endotoxin

Abstract: It is known that cells and organisms can indirectly "sense" changes in L-arginine availability via changes in the activity of various metabolic pathways. However, the mechanism(s) by which genes can be directly regulated by L-arginine in mammalian cells have not yet been elucidated. We investigated the effect of L-arginine in the in vivo model of peritoneal inflammation in mice and in vitro in RAW 264.7 macrophages. A detailed analysis of basic physiological functions and selected intracellular signaling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Therefore, the most interesting and promising candidate for L-arginine effect on macrophages is the GPRC6A receptor, the activation of which was found to be responsible for the L-arginine-mediated NO signaling in endothelial cells (Christiansen et al, 2007;Joshi et al, 2007). A similar pathway was documented for the L-arginine-mediated MAPK signaling in macrophages (Pekarova et al, 2013b). The activation of GPRC6A by extracellular L-arginine led to a significant increase in the LPS-stimulated macrophage NO synthesis.…”
Section: The Importance Of L-arginine Bioavailability For Macrophagesmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, the most interesting and promising candidate for L-arginine effect on macrophages is the GPRC6A receptor, the activation of which was found to be responsible for the L-arginine-mediated NO signaling in endothelial cells (Christiansen et al, 2007;Joshi et al, 2007). A similar pathway was documented for the L-arginine-mediated MAPK signaling in macrophages (Pekarova et al, 2013b). The activation of GPRC6A by extracellular L-arginine led to a significant increase in the LPS-stimulated macrophage NO synthesis.…”
Section: The Importance Of L-arginine Bioavailability For Macrophagesmentioning
confidence: 92%
“…Importantly, this also involves the activation of the innate , 1996). Importantly, it was demonstrated that the decrease in L-arginine concentration, occurring during inflammatory processes, could be associated with a significant reduction of NO levels released from activated macrophages (El-Gayar et al, 2003;Pekarova et al, 2011;Pekarova et al, 2013b). This phenomenon, which is crucially involved in the deregulation of innate immune responses, was described as the "L-arginine paradox."…”
Section: The Importance Of L-arginine Bioavailability For Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were transiently transfected with control siRNA and siRNA against caveolin-2 (all siRNA constructs were purchased from Santa Cruz Biotechnology, USA) using an electroporation system (Gene Pulser II, Bio-Rad Laboratories) as described previously (Pekarova et al, 2013a). There was no change in cell viability when compared macrophages transfected with control siRNA and macrophages transfected with siRNA against caveolin-2 (data not shown).…”
Section: Transfection Of Cells With Sirnamentioning
confidence: 99%
“…All experiments were conducted in C57BL/6J mice (males, 25-30 g, 12-14 weeks old) (Masaryk University, Brno, Czech Republic) housed in a temperature-controlled animal facility with 12 h light-dark cycle and free access to rodent chow. BMDMs and peritoneal macrophages (PMs) (used as a positive control) were isolated from mice according to standard protocols, described previously in more details (Pekarova et al, 2013a;Rudolph et al, 2010). BMDMs were grown in Dulbecco's Modified Eagle Media (DMEM), which were supplemented with culture medium from CCL-1 cells containing macrophage-colony stimulating factor (M-CSF) (ATCC, Manassas, VA, USA), 20% of fetal bovine serum (FBS, low endotoxin; PAA, Pasching, Austria), and 1% gentamycin.…”
Section: Cell Culture and Experimental Modelsmentioning
confidence: 99%